Fragmentasi Otoritas Religius di Ruang Digital: Studi Sosiologi Pendidikan Islam terhadap Praktik Pembelajaran Berbasis Media Sosial - Sabariah Sabariah; Sri Wahyuni; Muhammad Nur Alim; Muhammad Yaqub Hudawi Psrb; Khoirunnisa Lubis; Melda Khairani; M. Alfarizi (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The transformation of social media as a space for religious learning has changed the patterns of production, distribution, and legitimacy of Islamic knowledge. However, studies of the sociology of Islamic education still tend to view religious authority through an institutional framework that is inadequate to explain the increasingly decentralized dynamics of digital life. This study aims to analyze the transformation of religious authority in social media-based Islamic learning practices by focusing on legitimation mechanisms, changes in pedagogical relations, and the contestation of religious discourses formed within the digital ecosystem. The study uses a qualitative approach within a critical-sociological paradigm, drawing on library research, discourse analysis, and critical reviews of literature, academic studies, and narratives of religious learning that develop on social media. The results show that religious authority has shifted from the dominance of scientific credentials and institutional affiliations to one increasingly determined by algorithmic visibility, digital popularity, the intensity of interaction, and the performative ability of religious actors to attract audience attention. These changes have led to the emergence of a fluid, competitive, and multidirectional authority, thereby blurring the boundaries between formal and informal authority. At the same time, the production of Islamic knowledge is moving toward faster, more concise, and more easily consumed formats. Still, it is vulnerable to methodological simplification, fragmentation of understanding, and decontextualization of religious sources. Pedagogical relations are also shifting from a vertical transmission model to a participatory pattern that expands access to learning while weakening mechanisms for scientific verification. These findings suggest that religious authority in the digital space should be understood as a relational construct shaped by interactions among actors, technology, and audiences. Thus, a reconstruction of the sociological framework of Islamic education is necessary to respond to the changing ecology of contemporary religious learning.